A STUDY ON THE QUALITY AND CHARACTERISTICS OF CPO FROM MIXED OUTSPEC SOURCES - Tarigan, Bahtra Yudha; Lubis, Zulkifli; Elisabeth, Jenny (Universitas Medan Area, 2025)
Outspec CPO is Crude Palm Oil (CPO) that does not meet standard CPO quality specifications. Outspec CPO can still be blended with standard CPO, provided that the resulting mixture continues to meet acceptable quality criteria. This study aimed to evaluate the effects of different blending levels of outspec CPO (0%, 1%, 3%, and 5%) and storage durations (0, 4, 8, and 12 days) on the quality of blended CPO. The research was conducted using an experimental method arranged in a factorial completely randomized design. The parameters measured to assess the quality of the blended CPO were: FFA (Free Fatty Acid), PV (Peroxide Value) and DOBI (Deterioration of Bleachability Index). The results showed that the highest quality was achieved with a 0% outspec CPO blend and 0 days of storage, yielding: FFA: 3.10%, PV: 0.10 meq/kg and DOBI: 2.97. Conversely, the lowest quality was observed with a 5% outspec CPO blend and 12 days of storage, resulting in: FFA: 5.31%, PV: 25.45 meq/kg and DOBI: 1.28. These findings indicate that a higher percentage of outspec CPO and longer storage durations lead to increased FFA and PV values, while the DOBI value decreases.